2007
DOI: 10.1111/j.1469-1795.2007.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of waterbird colonies in southern Louisiana to recent drought and hurricanes

Abstract: Although hurricanes have been implicated in causing shifts in waterbird use of individual colonies, little is known about whether or not these effects are consistent across broader areas affected by a storm. We examined the effects of Hurricane Rita, and to a lesser extent Katrina, and a subsequent drought, on the nesting activity of waterbirds across colonies located in southern Louisiana. Using ground counts, we compared changes in numbers of nesting pairs between 2005 and 2006, the years encompassing the hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…As coastal development in the Gulf of Mexico increases, due to human populations growing and shifting toward coastal areas (Cendrero & Fischer 1997), habitat is gradually being replaced by man-made structures (Leu et al 2008). Habitat is also being lost to rising sea levels in the region, a problem exacerbated by increasing severity and frequency of hurricanes (Gornitz 1995, Webster et al 2005, Leberg et al 2007. With the species' apparent reluctance to move inland, management of reddish egret populations will be difficult if habitat continues to degrade.…”
Section: Discussionmentioning
confidence: 99%
“…As coastal development in the Gulf of Mexico increases, due to human populations growing and shifting toward coastal areas (Cendrero & Fischer 1997), habitat is gradually being replaced by man-made structures (Leu et al 2008). Habitat is also being lost to rising sea levels in the region, a problem exacerbated by increasing severity and frequency of hurricanes (Gornitz 1995, Webster et al 2005, Leberg et al 2007. With the species' apparent reluctance to move inland, management of reddish egret populations will be difficult if habitat continues to degrade.…”
Section: Discussionmentioning
confidence: 99%
“…Louisiana's coastal and offshore zones host infrastructure that supplies 90% of the U.S. outer continental shelf oil and gas resources (CPRA 2012), serving as a reminder of the potential threat of future spills. Natural threats such as hurricanes can also affect coastal nesting bird populations (Leberg et al 2007); such tropical storms have been shown to impact success of coastal restoration activities in providing habitat for nesting waterbird populations (Raynor et al 2013, Walter et al 2013.…”
mentioning
confidence: 99%
“…Previous studies have revealed large‐scale movements during the winter by many other migratory species, including waterfowl (Oppel et al 2008), raptors (Kochert et al 2011), passerines (Heckscher et al 2011, Renfrew et al 2013), and nightjars (Ng et al 2018, Tonra et al 2019). Similar to other wading birds, the winter relocations we observed may result from changes in water levels, prey availability, or be in response to hurricane impacts (Shepherd et al 1991, Bancroft et al 2002, Leberg et al 2007, Wunderle 2017, Bencoster et al 2019). Climate change is predicted to impact each of these three environmental factors in both the Caribbean (Biasutti et al 2012, Culp et al 2017) and Florida Everglades (Pearlstine et al 2010, Catano et al 2015), which could reduce the amount or quality of non‐breeding habitat for birds from the populations we studied.…”
Section: Discussionmentioning
confidence: 56%